Ultrafast and Ultrastable Heteroarchitectured Porous Nanocube Anode Composed of CuS/FeS2 Embedded in Nitrogen‐Doped Carbon for Use in Sodium‐Ion Batteries. Issue 6 (2nd December 2021) - Je, Junhwan; Lim, Hyojun; Jung, Hyun Wook; Kim, Sang‐Ok
Abstract: The enhancement of the structural stability of conversion‐based metal sulfides at high current densities remains a major challenge in realizing the practical application of sodium‐ion batteries (SIBs). The instability of metal sulfides is caused by the large volume variation and sluggish reaction kinetics upon sodiation/desodiation. To overcome this, herein, a heterostructured nanocube anode composed of CuS/FeS2 embedded in nitrogen‐doped carbon (CuS/FeS2 @NC) is synthesized. Size‐ and shape‐controlled porous carbon nanocubes containing metallic nanoparticles are synthesized by the two‐step pyrolysis of a bimetallic Prussian blue analog (PBA) precursor. The simple sulfurization‐induced formation of highly conductive CuS along with FeS2 facilitates sodium‐ion diffusion and enhances the redox reversibility upon cycling. The mesoporous carbon structure provides excellent electrolyte impregnation, efficient charge transport pathways, and good volume expansion buffering. The CuS/FeS2 @NC nanocube anode exhibits excellent sodium storage characteristics including high desodiation capacity (608 mAh g –1 at 0.2 A g –1 ), remarkable long‐term cycle life (99.1% capacity retention after 300 cycles at 5 A g –1 ), and good rate capability up to 5 A g –1 . The simple, facile synthetic route combined with the rational design of bimetallic PBA nanostructures can be widely utilized in the development of conversion‐based metal sulfides and other high‐capacity anode materials for high‐performance SIBs. Abstract : A facile, effective nanoconfinement of intermixed CuS/FeS2 in nitrogen‐doped carbon derived from bimetallic Prussian blue analogs (PBAs) enhances the structural stability and facilitates sodium‐ion diffusion by preventing particle aggregation and metal dissolution. These nanocubes demonstrate superior sodium‐ion storage performance and the synthetic approach based on bimetallic PBAs will promote the development of various heterostructured materials for energy storage applications.